Pistachio shells as remediating agents for uranium in contaminated industrial seawater. (June 2020) - Younes, Ali; Ali, Jafar Sunga; Nur, Mohamed Tousif; Duda, Artem; Wang, Jasmine; Samson, Jacopo; Kawamura, Akira; Francesconi, Lynn; Alexandratos, Spiro; Drain, Charles Michael
Abstract: Waterways have histories of being contaminated by heavy and/or radioactive metals produced by industrial processes. Natural radioisotopes of uranium ( 238 U, 235 U and 234 U), long-lived radiometals, are widespread in the environment as a result of both naturally occurring processes and anthropogenic processes. Uranium is considered a major threat to humans. Previous research has focused on using inorganic materials (e.g. ion-exchangers, extractants, nanoporous sorbents) to remove such metal. However, there has been a rise in using biodegradable, recyclable, and organic biological wastes to remove heavy toxic metals from aqueous solutions. The purpose of this study is to identify pistachio shells as good candidates for the removal of uranyl from aqueous solutions. The influences of pH, contact time, temperature, and initial uranyl concentration on uranyl uptake were investigated. The influence of pH was observed to be variable, with relatively high uptake occurring at pH 4 and at slightly alkaline pH values. Uptake increased as a function of contact time, temperature, and initial uranyl concentration. The mechanism followed pseudo-second-order and intraparticle kinetics models, and the shell was demonstrated to be a Freundlich isotherm. The shells were successfully demonstrated to be viable adsorbents for uranium in seawater samples, with obtained trends similar to those achieved in the batch studies. Graphical abstract: Image 1 Highlights: Evaluation of pistachio shell (PS) as an extractant of uranyl from aquatic medium. PS has a good selectivity and affinity for uranyl (U). The adsorption kinetics of uranyl onto PS is dependent on contact time. PS adsorption mechanism exhibits pseudo-2nd-order and intra-particle kinetics. PS was demonstrated to be viable adsorbents for uranyl in applied seawater samples.